Differences in shooting accuracy and efficiency trends of the best handball representations at the 2021 Tokyo Olympic Games - Bajgoric, S.; Dug, M. (Sport Scientific and Practical Aspects - International Scientific Journal of Kinesiology, 2022)
This study has been undertaken to perform the game analysis, to determine an efficacy difference in an offence of four first placed woman handball national teams at the Olympic games in Tokyo. One of the problems, which undergoes scientific research, is competition between teams and an efficacy in the mentioned sport. The performance of any technical element in the handball is impossible to perform without the adequate motoric ability, as well as the quality of the motoric ability is impossible to perform without the rational technique. In this study, based information were obtained from first THIRD handball national teams of France, Russia and Norway during eight matches at the Olympic games in Tokyo. The total of 12 offence`s variables were obtained from 8 matches of woman`s handball national teams and analysed: total number of shots (sut_uk), precise - efficient number of shots (sut_pre), total number of shots from 6 meters (sut_m6_uk), precise - efficient number of shots from 6 meters (sut_m6_pre), total number of shots from wings (sut_kril_uk), precise - efficient number of shots from wings (sut_kr_pre), total number of shots from 9 meters (sut_m9_uk), precise - efficient number of shots from 9 meters (sut_m9_pre), total number of shots from 7 meters (sut_m7_uk), precise - efficient number of shots from 7 meters (sut_m7_pre), total number of fast centres (brzc_uk) and total number of precise - accomplished fast centres (sut_brzc_pre). Based on the analysis in this study, it is evident that the game of national teams was based on shots from 9 m, shots from 6 m, and on the fast performance of the fast centre. By analysed results, could be concluded, that these variables significantly determinate the game in offence on this tournament.